Neurofibroma of the Breast Detected on Positron Emission Tomography-CT in a Patient with Neurofibromatosis Type 1: A Case Report - Hoseok Lee; Hye Jung Kim; Bora Yang; So Mi Lee; Ji Yun Jeong (대한영상의학회지, 2016)
Neurofibromas of the breast are rare. They are commonly found as solitary lesions or parts of neurofibromatosis type 1 and are usually located on the nipple-areolar area. We describe a case of neurofibroma of the breast in the retromammary space, which was detected on positron emission tomography-computed tomography after hysterectomy due to endometrial cancer.